Significance of D-Dimer in Acute Ischemic Stroke Patients With Large Vessel Occlusion Accompanied by Active Cancer - Pan, Kwang Hyun; Kim, Jaeyoun; Chung, Jong-Won; Kim, Keon Ha; Bang, Oh Young; Jeon, Pyoung; Kim, Gyeong-Moon; Seo, Woo-Keun (Frontiers in Neurology, 2022)
Background: This study aimed to investigate clinical outcome predictors of acute stroke patients with large vessel occlusion and active cancer and validate the significance of D-dimer levels for endovascular thrombectomy decisions. Methods: We analyzed a prospectively collected hospital-based stroke registry to determine clinical EVT outcomes of acute stroke patients within 24 hours with following criteria: age≥18 years, NIHSS≥6, and internal carotid artery or middle cerebral artery lesion. All patients were classified into EVT and non-EVT groups. Patients were divided into two groups by initial D-dimer level. We explored variables potentially associated with successful recanalization as well as 3-month functional outcomes and mortality rates. Results: Among 68 patients, 36 were treated with EVT, with successful recanalization in 55.6%. The low D-dimer group showed a higher rate of successful recanalization and favorable outcome than the high D-dimer group. The mortality rate was higher in the high D-dimer group. No EVT and high D-dimer level were independent predictors of mortality, whereas lesion volume and low D-dimer level were independently associated with favorable outcomes. Conclusions: D-dimer level is a prognostic factor in acute LVO stroke patients with active cancer, and its high value for EVT decisions provisionally supports its testing in this patient population.